The Influence of Work Motivation and Discipline on Teacher Performance at the Pustek Serpong Vocational School in South Tangerang - Muhammad Ramdhan (Universitas Negeri Makassar, 2022)
This study aims to determine the effect of motivation and work discipline, either partially or simultaneously on teacher performance at Pustek Pustek Serpong, South Tangerang. In this study, the sampling technique used a saturated sample, which amounted to 60 respondents. The data analysis methods used are Validity Test, Reliability Test, Heteroscedasticity Test, Multicollinearity Test, Autocorrelation Test, Normality Test, Correlation Coefficient, Coefficient of Determination, Multiple Linear Regression, Partial significant test (t test) and simultaneous significant test (F test). The results of the study indicate that motivation and work discipline have a positive and significant effect on teacher performance with a contribution of 56.1% influence while the remaining 43.9% is influenced by other factors not examined in this study. From the results of the hypothesis test, it shows that the Fcount value of 36.423 is greater than Ftable of 3.16 with a significant level of 0.000 less than 0.05. So it can be concluded that simultaneously motivation and discipline have a significant and significant effect on teacher performance.